Dynamic posturography findings among patients with liver cirrhosis in Egypt - Wael M. Aref; Noha A. Hosni; Mohamed Naguib; Mohamed El-Basel (SpringerOpen, 2012)
Background Liver cirrhosis is a condition that destroys the normal function of the liver, leading to hepatic encephalopathy, which is associated with impairment in postural control and disturbance in balance. Aim of the studyThe aim of this study was to detect the disturbances in balance and postural control because of hepatic encephalopathy as a result of liver cirrhosis using dynamic posturography. Participants and methodsIndividuals were divided into two groups: 45 patients with liver cirrhosis and 45 controls. Both groups underwent dynamic posturography to evaluate balance control, number connection test-type A, line tracing test, and serum ammonia (NH3) level to assess encephalopathy. Results Dynamic posturography findings were significantly weaker in patients with liver cirrhosis than in the controls. They were also weaker in patients with high NH3 than in patients with low NH3. There were significant negative correlations between dynamic posturography findings and number connection test-type A, line tracing test, and NH3 levels. Conclusion Hepatic encephalopathy because if liver cirrhosis affects balance control and the degree of affection is related to the degree of encephalopathy.